1991
DOI: 10.1071/mf9910069
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of an ectoparasitic gastropod, Hypermastus sp. (Eulimidae), on the sand dollar, Arachnoides placenta (Echinoidea)

Abstract: The association between the sand dollar, Arachnoides placenta, and the eulimid gastropod, Hypermastus sp., was investigated at Pallarenda Beach, Townsville, Queensland. Hypermastus sp. is a temporary ectoparasite of A. placenta that penetrates the latter's test to ingest gonad tissue and coelomic fluid. The infestation rate normally varies between 8 and 15% but increases in winter to 26%. This seasonal increase in the infestation rate appears to be due to an increase in the duration of attachment of female par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It was suggested that some individuals of H. obliquistomum develop directly to females, while others pass through a male phase (Warén et al , 1994) since there are two forms in large females and the more slender of the two has a vestigial penis and a well-developed pallial oviduct. Both H. placentae and H. tenuissimae were suggested to change sex from male to female because large males equivalent to mature females in size were occasionally found (Crossland et al , 1991; Warén & Crossland, 1991). Though overlapping of size distributions of mature males and females were detected in this study (Table 2), no evidence for H. tokunagai changing sex could be obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that some individuals of H. obliquistomum develop directly to females, while others pass through a male phase (Warén et al , 1994) since there are two forms in large females and the more slender of the two has a vestigial penis and a well-developed pallial oviduct. Both H. placentae and H. tenuissimae were suggested to change sex from male to female because large males equivalent to mature females in size were occasionally found (Crossland et al , 1991; Warén & Crossland, 1991). Though overlapping of size distributions of mature males and females were detected in this study (Table 2), no evidence for H. tokunagai changing sex could be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have found important ecological aspects of eulimids (e.g. Elder, 1979; Fujioka, 1985; Crossland et al , 1991) but our knowledge is not enough to understand the complex life history traits of eulimids.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the close relationship between infestation and recruitment also suggests infestation is seasonal, with peaks in the middle of the warm season, shortly after each recruitment. Seasonal variation in infestation has been observed in eulimidechinoderm associations (Morton 1979, Crossland et al 1991. However, in such associations, seasonal variability is not due to juvenile recruitment but to variability in nutrient supply.…”
Section: Discussionmentioning
confidence: 99%
“…Predators and parasites of echinoids include gastropods (Moore 1956;Chesher, 1969;Hughes and Hughes, 1971;Hendler, 1977;Gladfelter 1978;Serafy, 1979;Warén, 1980a;Warén, 1980b;Hughes, 1981;Kier, 1981;Warén et al 1983;Fujioka, 1985;Alekseev and Endelman, 1989;Levitan and Genovese, 1989;Warén and Moolenbeek, 1989;Warén and Mifsud, 1990;Warén and Crossland, 1991;Crossland et al, 1991Crossland et al, , 1993McClintock and Marion, 1993;Oliverio et al, 1994;Rinaldi and Malacologico, 1994;Warén et al, 1994;McClanahan, 1999;Nebelsick and Kowalewski, 1999;Ceranka and Złotnik, 2003;Vaïtilingon et al, 2004;Złotnik and Ceranka, 2005a, b;Neumann and Wisshak 2009;Meadows et al, 2015), polychaetes (Wisshak and Neumann, 2006), crustaceans (Tegner and Levin, 1983;Smith, 1984;Wirtz et al, 2009) including barnacles (Madsen and Wolff, 1965;Cross and Rose, 1994;Donovan et al, 2016) and copepods (Margara, 1946;Roman, 1954), echinoderms (Merril and Hobson, 1970;…”
Section: Introductionmentioning
confidence: 99%